Fluid Responsiveness by Femoral Artery Doppler in Septic Shock: Validation with Trans-Thoracic Echocardiography - Walid Omar; Osama Abbas; Suzy Fawzy; Mohammed Afify (Egyptian Journal of Critical Care Medicine)
Abstract Background The femoral arterial Doppler is quite simple and usually bypass the limitations of trans-thoracic echocardiography (TTE) in evaluation of hemodynamic response to volume resuscitation. Objective Evaluation of the use of femoral artery Doppler as an alternative to TTE in assessment of cardiac response to fluid challenge (FC) in critically ill patients with septic shock. Methods In an observational prospective study, 50 adult patients with septic shock were admitted to the critical care department. After the FC and the echocardiographic assessment, they were classified into two groups by percent change of velocity time integral over left ventricular outflow tract (%VTIAo). Included patients were sub-grouped into fluid responder “R group” if % VTIAo ≥ 15% and fluid non-responders “NR group” if %VTIAo < 15%. All hemodynamic, echocardiographic and femoral Doppler parameters were measured before and after FC. Primary outcome was the accuracy of femoral arterial Doppler, namely percent change of femoral velocity time integral and femoral maximum velocity (%VTIF and %VFmax) in determining R and NR patients after FC. Secondary outcomes were ICU length of stay and 28-days mortality. Results The mean age of all enrolled patients was 66.18 years, 44% were males. By %VTIAo, 30 patients were fluid responder while 20 patients were not. %VTIF increase over 10% was a good predictor to predict the fluid responders with (AUC = 0.817) (95% CI, 0.699–0.934, P <.0001). But, %VFmax increase over 7% was an excellent predictor (AUC=0.958) (95% CI; 0.891–1.000, P <.0001). %VFmax was more sensitive (80%) and %VTIF was more specific (95%). %VTIF and %VFmax showed a positive correlation with %VTIAo of 0.733 and 0.543, respectively (P = <.001 for both). Secondary outcome showed no 28-mortality difference, but significant shorter ICU stay in R (7.40±5.424) than in NR group (4.55±2.235) (P = .031). Conclusion Using femoral Doppler parameters could be a good simple tool to assess hemodynamic response to FC in septic shock. It could be taken as an alternative approach to TTE in assessing fluid responsiveness.